HABERMAS' PHILOSOPHY OF LIBERATION - Pereppaden, Jose (Journal of Dharma, 1997)
Jurgen Habermas (1929-) is a radical and systematic thinker who has made a remarkable attempt to formulate a radical philosophy of liberation. The intellectual environment of Habermas' thoughts is the critical social theories of the famous Frankfurt School of which he is perhaps the most prominent member. The other important thinkers of this School are Herbert Marcus, Adorno, Horkheimer, Friederick Pollock, Erich Fromm, Franz Newmann, Loe Lowenthal; Walter Benjamin and Karl Otto-Apel. They were trying to establish a critical social theory (or philosophy) drawing inspiration from the classical critical thinkers such as Kant, Hegel, Marx, Freud, Max Weber and so on.